2019
DOI: 10.1039/c8bm01253a
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-derived stem cell-secreted factors promote early stage follicle development in a biomimetic matrix

Abstract: ADSCs encapsulated in biomimetic PEG hydrogels maintain stemness and secrete survival- and growth-promoting factors that support in vitro folliculogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…It is reported that several types of MSCs (PD-MSCs, UCMSCs, ADSCs) or their secretions are effective in improving ovarian function [17][18][19][20][21][22][23][24][25]. As a member of MSC family, if hAMSCs showed any difference from other type of MSCs?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that several types of MSCs (PD-MSCs, UCMSCs, ADSCs) or their secretions are effective in improving ovarian function [17][18][19][20][21][22][23][24][25]. As a member of MSC family, if hAMSCs showed any difference from other type of MSCs?…”
Section: Discussionmentioning
confidence: 99%
“…Thus, treatments effective in resisting ROS may promise to improve the quality of oocytes in AR-DOR patients [ 16 ]. In recent years, investigators have disclosed that transplantation of mesenchymal stem cells (MSCs) or their secretions, including placenta-derived mesenchymal stem cells (PD-MSCs) [ 17 ], human umbilical cord mesenchymal stem cells (UCMSCs) [ 18 , 19 ], adipose-derived stem cells (ADSCs) [ 20 , 21 ], or ADSC-conditioned medium [ 22 ], can all significantly improve ovarian function in premature ovarian failure (POF) or primary ovarian insufficient (POI) models. Furthermore, it is reported that transplantation of UCMSC functions on POI patient [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…112 Moreover, the growth of follicular diameter in in vitro models requires biomaterials that can provide good architecture, diffusion of nutrients, and biocompatibility. 91,113 In vitro studies of artificial ovaries for fertility preservation have used fibrin as a supporting biomaterial due to its physical properties and crosslinking ability (Table 3). 80 However, this biomaterial has low mechanical strength compared with other polymers, and it needs to be combined with other natural or synthetic polymers to mimic the cell microenvironment.…”
Section: Reviewmentioning
confidence: 99%
“…80 When mouse follicles were encapsulated in a fibrin alginate mixture, the hydrogels provided excellent architecture for cell attachment, proliferation, differentiation, and cell-cell signaling. 114 In vitro models of the ovary have also used alginate 58,90 or PEG 113,115 as supporting materials. These biomaterials also promote the survival, maturation, and autonomous function of follicles.…”
Section: Reviewmentioning
confidence: 99%
“…Thus, treatments effective in resisting ROS may promise to improve the quality of oocytes in AR-DOR patients [16]. In recent years, investigators have disclosed that transplantation of mesenchymal stem cells (MSCs) or their secretions, including placenta-derived mesenchymal stem cells (PD-MSCs) [17], human umbilical cord mesenchymal stem cells (UCMSCs) [18,19], adipose derived stem cells (ADSCs) [20,21] or ADSCs conditioned medium [22] all can signi cantly improve ovarian function in premature ovarian failure (POF) or primary ovarian insu cient (POI) models. Furthermore, it is reported that UCMSCs is function on POI patient [23].…”
Section: Introductionmentioning
confidence: 99%